The conflict-growth nexus in Fragile States: Empirical evidence from Somalia - Hassan, Arab Dahir; Saidy, Salim (International Journal of Social Sciences Perspectives, 2026)
This study examines the long-term impact of armed conflict on Somalia’s economic growth from 1997 to 2022, addressing the limited country-specific evidence on the conflict-growth nexus in fragile states. Annual data from the World Bank and the Uppsala Conflict Data Program are utilized, with conflict intensity measured by conflict-related deaths. The cointegration test confirms a stable long-run relationship, indicating that cointegration techniques are the appropriate estimation method. The results reveal that armed conflict has a substantial adverse effect on economic growth, as increased conflict reduces GDP through capital destruction, labor displacement, and weakened investor confidence. On the other hand, foreign aid positively supports economic growth through developmental projects and budget support, while unemployment negatively affects growth. Persistent unemployment erodes hope and drives the young generation toward risky migration routes to Europe, yet it does not compensate for the losses from sustained violence. The findings highlight the severe economic costs of insecurity and underscore that sustainable peace and institutional rebuilding are prerequisites for recovery. This study contributes to the fragile states literature by empirically examining Somalia’s conflict-growth dynamics and offering policy-relevant lessons for conflict resolution and targeted economic interventions.